ANALYSES OF WATER TABLE DEPTHS VARIATIONS IN AN OUTCROP AREA OF THE GUARANI AQUIFER SYSTEM IN BROTAS/SP-BRAZIL - Manzione, Rodrigo Lilla; Soldera, Bruna Camargo; Paes, Claudiane Otilia; Wendland, Edson (IRRIGA, 2015)
ANALYSES OF WATER TABLE DEPTHS VARIATIONS IN AN OUTCROP AREA OF THE GUARANI AQUIFER SYSTEM IN BROTAS/SP-BRAZIL RODRIGO LILLA MANZIONE 1; BRUNA CAMARGO SOLDERA 2; CLAUDIANE OTILIA PAES 3 E EDSON WENDLAND 4 1 UNESP/OURINHOS – São Paulo State University, Ourinhos, SP, Brazil. Email: manzione@ourinhos.unesp.br 2 UNESP/FCA – São Paulo State University, Botucatu, SP, Brazil. Email: brusoldera@hotmail.com 3 UNESP/FCA – São Paulo State University, Botucatu, SP, Brazil. Email: claudianepaes@hotmail.com 4 Department of Hydraulics and Sanitation – USP/EESC – University of São Paulo, São Carlos, SP, Brazil. Email: ew@sc.usp.br 1 ABSTRACT Several factors may influence variations in ground water levels. Some of these factors present static behavior while others present dynamic changes over time. The differences in management operations in agricultural sites, plant development and agricultural practices have direct impact on the unsaturated zone, as the levels of recharge and water tables can respond differently due to local conditions. Different information sources may be used and integrated in a statistical model to reveal the responses of ground water levels under certain conditions. Understanding these processes involves meeting a way of representing correlated variables together to form a new and smaller set of derived variables with minimum loss of information, removing redundancy or duplication. The objective of this study was to analyze the variations in water table depths using information from a groundwater monitoring network in an outcrop area of the Guarani Aquifer System (GAS) in Brotas, São Paulo, Brazil, associated with soil, vegetation and terrain variables, which possibly influence the groundwater dynamics. A factorial analysis was applied to identify the underlying factors which would explain this pattern of correlation within these sets of study variables. The main factors influencing the variations in water table over the monitoring period were as follows: sand particle size, terrain attributes, soil texture, soil and crop management and vegetation. This methodology can be useful for groundwater management, policy making and regulation of soil use in watersheds, and regional studies, for example, maximizing information in data analysis. Keywords: factorial analysis, statistical modeling, recharge, Brazil MANZIONE, R.L.; SOLDERA, B.C.; PAES, C.O.; WENDLAND, E. ANÁLISES DAS VARIAÇÕES DOS NÍVEIS FREÁTICOS EM UMA ÁREA DE AFLORAMENTO DO SISTEMA AQUÍFERO GUARANI EM BROTAS/SP-BRASIL 2 RESUMO Diversos fatores influenciam as variações de níveis freáticos. Alguns desses fatores apresentam comportamento estático enquanto outros apresentam mudanças dinâmicas ao longo do tempo. As diferenças nas operações de manejo do solo em áreas agrícolas, desenvolvimento de plantas e práticas agrícolas tem impactos diretos na zona não saturada uma vez que os níveis de recarga e lençóis freáticos podem responder a condições locais. Diferentes fontes de informação podem ser usadas e integradas em um modelo estatístico para revelar a resposta dos níveos de águas subterrâneas sob certas condições. Entender esses processos envolve encontrar uma maneira de representar variáveis correlacionadas juntas para formar um novo e menor conjunto de variáveis derivadas com uma perda mínima de informação, removendo redundâncias ou duplicações. O objetivo desse estudo foi analisar as variações dos níveis freáticos usando informações de uma rede de monitoramento de águas subterrâneas em uma área de afloramento do Sistema Aquífero Guarani (SAG) em Brotas, São Paulo, Brasil associadas a variáveis de solo, vegetação e terreno que possivelmente influenciem a dinâmica das águas subterrâneas. Foi aplicada a análise fatorial para identificar fatores que expliquem o padrão de correlação entre esse conjunto de variáveis observadas. Os principais fatores influenciando a variação dos níveis freáticos durante o período monitorado foi o tamanho da fração areia, atributos de terreno, textura do solo, manejo dos solos e culturas e vegetação. Essa metodologia pode ser útil para a gestão das águas subterrâneas, formulação de políticas e regulação do uso do solo em bacias hidrográficas e estudos regionais, por exemplo, maximizando as informações na análise de dados. Palavras-chave: análise fatorial, modelagem estatística, recarga, Brasil